Downregulation of Gabra4 expression during alcohol withdrawal is mediated by specific microRNAs in cultured mouse cortical neurons. Issue 8 (2nd June 2015) - Bekdash, Rola A.; Harrison, Neil L.
Abstract Background Alcohol abuse and dependence are a serious public health problem. A large number of alcohol‐regulated genes, (ARGs) are known to be influenced by alcohol use and withdrawal (AW), and recent evidence suggests that neuroadaptation to alcohol may be due in part to epigenetic changes in the expression of ARGs. Gabra4, which encodes the α4 subunit of GABAA receptors (GABAARs), is one of a number of ARGs that show remarkable plasticity in response to alcohol, being rapidly upregulated by acute alcohol exposure. This study addressed the effects of AW on changes in the expression of Gabra4 and related genes that encode other subunits of GABAARs, and the potential regulation of Gabra4 by microRNAs. Methods We studied gene and microRNAs expression, using RT‐PCR and microRNA microarray in cultured cortical neurons treated with alcohol, which was then removed in order to simulate AW in vitro. We also used microRNA mimics or inhibitors, and a promoter‐reporter construct carrying the 3′UTR of Gabra4. Results Eleven hours after removal of alcohol, Gabra4 was downregulated, with a modest increase in the expression of Gabrg2, but no change in the expression of Gabra1, Gabrd, or Gabrb2. microRNA profiling in neurons undergoing AW revealed upregulation in the expression of miR‐155, miR‐186, miR‐24, and miR‐375 after 8 h of AW. Transfection with molecular mimics of miR‐186, miR‐24, or miR‐375 also downregulated Gabra4 expression, whereas transfection with the corresponding inhibitors of these microRNAs normalized Gabra4 expression in AW neurons to the level measured in control neurons. Promoter‐reporter experiments supported the idea that miR‐155, miR‐186, miR‐24, miR‐27b, or miR‐375 bind to the 3′UTR of Gabra4 and thereby inhibit protein production. Conclusions Our data suggest that AW decreases Gabra4 expression, and that this may be mediated in part by the induction of specific microRNAs in cortical neurons during AW.